Effect of different sealer cements on the push-out bond strength of fiber glass posts cemented by two resin cements (Brazilian Journal of Health Research, 2025)
Introduction: There is not a consensus in the academic environment regarding the factors that can influence the adhesion of glass fiber posts to root dentin. Objectives: Aim to evaluate the influence of different sealer cements on the bond strength of fiberglass posts cemented by two resin cements (adhesive and self-adhesive). Methods: A sample of 80 bovine incisors were divided into four groups (n=20). The sealer cements were: Group I - zinc oxide and eugenol (Endofill), Group II: resin (AH plus) and Group III: MTA (Fillapex) and Group IV: control (gutta percha). 10 elements in each group underwent conventional cementation with adhesive resin cement (Relyx ARC) and the other 10 self-adhesive cement (Relyx U200). The specimens were subjected to 2 mm transverse sections to assess the push-out test and analysis of stereoscopic microscopy. Data were analyzed statistically using the Kruskal-Wallis and Chi-square (p0 .05). Relyx ARC showed all fractures focused on standard cement adhesive bonding. To Relyx U200, all groups focused their fractures in standard cement-dentin adhesive, but group 2B (U200 Plus AH) demonstrated a greater number of cohesive bonding fractures. Conclusion: Sealer Endofill decreased the bond strength of Relyx ARC. Different sealers employed did not influence the bond strength of posts cemented with U200. The two resin cements showed similar performances in different areas of root dentin.
Keywords: Dentin; Post and Core Technique; Cementing